Reliable universal RT-PCR assays for studying influenza polymerase subunit gene sequences from all 16 haemagglutinin subtypes - Li, Olive T.W.; Barr, Ian; Leung, Connie Y.H.; Chen, Honglin; Guan, Yi; Peiris, J.S. Malik; Poon, Leo L.M. (Journal of virological methods, 2007)
Realizable one-step RT-PCR assays specific for influenza PB2, PB1 and PA segments are described in this report. The designs of the consensus primers were based on more than five thousands polymerase genes derived from avian or mammalian viral strains. All the viral RNA tested in this study could be consistently amplified by the assays. The reaction products were specific and could be used for direct DNA sequencing. These assays might be useful tools to study the sequences of these genes.